Sophia : the cliffs - Foreman, Richard (New York : Tzadik, 2009)
[Sophia: the cliffs]: An early play by avant-garde theater pioneer Richard Foreman, whose "notion at the time was a theater that at every moment confronted the audience with the sheer 'presence' of performer, text, music."##[35+ year retrospective compilation]: A broad selection of scenes culled form the entire history of the Ontological-Hysteric Theater.
film
Keywords: Foreman, Richard